Emotional regulation among children with autism: Narratives from home learning partners during COVID-19 - Mandap, Donna C. (Animo Repository, 2022)
This study primarily explores the narratives of the Home Learning Partners (HLPs) of children with autism during the COVID-19 pandemic. It attempts to establish a more profound understanding of the challenging situations that contribute to the emotional regulation of children with autism, including the support they have received from their parents and household members. The pandemic repercussions, such as lockdowns, physical/social distancing, mandatory quarantine and use of face masks and face shields, and the closure of establishments, including therapy centers and schools, have been documented in the literature. There is, however, a dearth of qualitative studies written about the observed challenges of children with autism, the support they received, and the realizations made by their HLPs. This study delves into these prevailing concerns while providing real-life narratives centered on the HLPs’ experiences. It likewise aims to offer other HLPs a shared and relatable account of experiences to help them assist their children with autism who encounter emotional dysregulations during dire times. Through the creative yet real-life narratives, the study involves issues that may interest the local government and the Department of Education policymakers to address. A qualitative research design, specifically narrative inquiry, was mainly used to elicit meaningful stories and draw insights. Guided by the intra-paradigm and multi-phase procedures, the researcher employed one-on-one in-depth interviews with twelve HLP participants, two of which are household members. The participants wrote succinct diary entries and answered a demographic profile form to substantiate the interview data. The HLPs produced brief records of their children’s behaviors for two weeks. The researcher anchored in Polkinghorne’s (1995) Narrative Analysis principles, where the in-depth interview transcripts underwent rigorous coding procedures, such as narrative and descriptive coding. The researcher categorized and synthesized the data to produce initial stories that went through a process called “narrative smoothing,” which constructed the emplotted narratives of support for their children with autism and the challenges their children encountered during the height of the COVID-19 pandemic. This study discovers challenging situations that have contributed to the emotional regulation of children with autism, as follows: (a) being quarantined at home 24/7; (b) too much screen time; (c) remote learning; (d) lack of activities to do at home; (e) limited access to preferred food; (f) contracting health issues; (g) disrupted routines; (h) change of location; and (i) a chaotic home environment. As the children encountered these challenging situations, they manifested various responses, such as (a) aggression, which includes injurious behaviors, frequent shouting, screaming, and crying; anger issues, frustration, and irritation, frequent mood swings, and impatience; (b) enjoying longer screen time; (c) yearning to go out; (d) excessive eating; (e) difficulties in adjustment/doing old routines; (f) increase self-stimulating behaviors/exhausting energy; (g) frequent self-inflicting/self-injurious; (h) disinterest in remote learning; (i) preferring to stay indoors; (j) regulating behaviors like saying sorry; (k) developing new interests and bonding with siblings and grandparents, and (m) expressing wants and needs. The findings also reveal that despite the difficulties in children with autism’s emotional regulation, their HLPs were able to support them as they went through trying times. They provided and cared for their children with positive and negative reinforcements. The study further discusses implications and recommendations for the local government, Schools Division Office policymakers, SPED and inclusive education teachers, home learning partners, and future researchers to prioritize supporting families with children with special needs by reflecting on and evaluating current programs, strategies, and pedagogies. Keywords: Children with autism, Emotional Regulation, Emotional Dysregulation, COVID-19 Pandemic, Home Learning Partner